Glycyrrhiza polysaccharide attenuates Neospora caninum-induced intestinal epithelial cell damage by the C/EBPβ/IL-17/TNF signaling pathway - Wang, Shuai; Meng, Sudan; An, Yongsheng; Qian, Weifeng; Ma, Yanbo; Guo, Shuai; Zhang, Cai (Frontiers in Veterinary Science, 2026)
Intestinal epithelial cell (IEC) damage is a crucial event in pathogen-induced intestinal inflammation and systemic pathological responses, and their functional integrity directly affects animal health. This study used bovine intestinal epithelial cells (BIECs-21) and mouse models to examine the protective effects of Glycyrrhiza polysaccharide (GCP) against Neospora caninum (NC)-induced IEC damage and investigate its underlying mechanisms. In vitro, BIECs-21 were infected with NC to establish an intestinal epithelial injury model. In vitro experiments revealed that GCP pretreatment effectively inhibited NC infection-induced decreases in cell viability and lactate dehydrogenase (LDH) release, preserving intestinal epithelial homeostasis. Transcriptomic analysis results showed that NC infection activated the interleukin (IL)-17 and tumor necrosis factor (TNF) signaling pathways, increasing the expression of chemokines (CXCL1/2/3) and inflammatory genes (FOSB). In contrast, GCP inhibited the expression of transcription factors CCAAT/enhancer-binding protein β (C/EBPβ) and FOS, reduced pro-inflammatory factors (e.g., IL-6, IL1RAP), and mitigated excessive inflammatory responses. In vivo experiments confirmed that low-dose GCP intervention significantly reduced intestinal hemorrhage and edema, decreased parasite loads in intestinal and cerebral tissues of infected mice, and suppressed protein expression of IL-17RA, TNF-α, p-C/EBPβ and p-NF-κB in intestinal tissues. These findings demonstrate that GCP mitigates NC-induced IEC injury by modulating intestinal immune homeostasis through the C/EBPβ/IL-17/TNF signaling pathway, thus establishing a theoretical basis for developing natural therapeutics against pathogen-induced gut damage.